아토피 피부염 환자에서 黃連解毒湯이 함유된 한방화장품에 대한 임상 연구 - 윤대철(Dae Chul Yun); 김희택(Hee Taek Kim); 김이화(Ee Hwa Kim); 호동수(Dong Su Ho) (동의생리병리학회지, 2008)
This clinical research was conducted to test patients with Atopic Dermatitis by external application with Hwangryeonhaedok-Tang in cosmetics. We gave scores to 31 patients who visited the Dept. of Oriental Medical Opthalmology & Otolaryngology & Dermatology of Semyung University Jecheon Oriental Medical Hospital from May 15th, 2008 to June 26th. Fifteen patients were treated with the ointment that contain Hwangryeonhaedok-Tang (experimental group) and sixteen patients were treated with normal ointment that doesn't have Hwangryeonhaedok-Tang (control group) for 4 weeks. We observed change of total IgE, eosinophil count, Skin Temperature, Transepidermal Water Loss(TEWL), Skin Hydration and Skin pH. Also Clinical Index of Atopic Dermatitis(SCORAD Index) and global assesment of efficacy were used to evaluate the effects of Hwangryeonhaedok-Tang. Statistical analysis was performed by using frequency analysis and descriptive analysis. Statistical significance was achieved if the probability was less than 5%(p<0.05). After 4 weeks of external application treatment, SCORAD Index in experimental group was significant statistically decreased compared with control group. After 4 weeks of external application treatment, total IgE of both groups were decreased and eosinophil count in control group was decreased but experimental group was unstatistically decreased. Unstatistically, both groups didn't showed significant effect on Skin Temperature. Transepidermal Water Loss(TEWL) in both groups were increased but experimental group was significant decreased compared with control group. Skin Hydration in experimental group was significant statistically increased compared with control group. Statistically, both groups didn't showed significant effect on Skin pH. Only experimental group showed little increase. After 4 weeks of external application treatment, experimental group showed significant effect on global assesment of efficacy. Considering the above results, we can speculate that cosmetics with Hwangryeonhaedok-Tang has some therapeutical effects in mitigating the symptoms of Atopic Dermatitis. KCI Citation Count: 11